PETRUK DADI RATU SIMBOL PERLAWANAN RAJA-RAJA JAWA - Juwono, Harto (Institut Seni Indonesia Surakarta, 2024)
This article is the result of literature study and archival research which is carried out with the aim of revealing the meaning and impact of the existence of the story of Petruk Dadi Ratu in the world of Javanese culture and politics during the king regime. In an atmosphere of structural domination by the colonial regime, the emergence of wayang and stories represented a response from the kings and the societies through arts and culture towards colonial hegemony. For this reason, the method used in this research is a structural history methodology which also includes historical research methods, with a semiotic approach to obtain appropriate interpretation results on the symbolism attached to the object. The data used in this paper is textual data as well as observing the form of the Petruk puppet as a king in both Surakarta and Yogyakarta styles. As a conclusion from this research, Petruk Dadi Ratu is a successful form of Javanese response in the aesthetic values that grow in its arts and cultures towards the forms of foreign power in all areas of life.